Narrar o vivido, viver o narrado : a construção do diário na obra de Jonas Mekas - Valles, Rafael Rosinato (2018)
This thesis carries out a study of the diary in the work of Jonas Mekas, throughout three formats: the written diary, the diary-film and the video diary. The aim is to analyze how Mekas’s work contributes to an understanding of the diary as a narrative form, and how the author constructs his process of self-representation by means of the diaries. This work seeks to establish a definition for the diary, by means of theoretical references related to the spheres of literature (Braud, 2006; Simonet-Tenant, 2004; Girard, 1986; Lejeune, 2015; Blanchot, 2005) and of audiovisual work (James, 2013; Renov, 1996). As object of study, we analyze the book I had nowhere to go (1991), the diary-films Lost Lost Lost (1976), Walden – Diaries, Sketches & Notes (1969), Reminiscences of a Journey to Lithuania (1972), and video diaries from the 365 Day Project (2007). This thesis takes weavings (Daney, 2007; Benjamin, 1994) and rends (Daney, 2007; Didi-Huberman, 2014, 2015) as its methodology, grounding itself on the way in which Mekas elaborates his narrative choices and his historical condition. We conclude that Mekas’s work points to an understanding of the diary not solely as literary genre, but as a narrative that affirms itself in a plurality of forms, following the shifts done by the author in his relation to time, space, and the use of different technical devices. We also conclude that Mekas, in his diaries, builds an intrinsic relation between narrating the lived and living the narrated, which reveals how the diaries not only document a certain socio-historical context, but are also themselves part of that context and of the subjectivity built by their author.